Pictorial cognitive task solving and dynamics of event - related desynchronization - Petrek, Josef (Biomedical papers, 2009)
AIMS: To analyze the event-related desynchronization/synchronization (ERD/ERS) attended with the mental load arising while solving two cognitive tasks. The features of the presented visual stimulus determined the type of cognitive task that should be solved.METHODS: For each experimental task and everybody's subject FFT Analysis module calculated the total power histograms from a fixed frequency band (3-20 Hz or 8-13 Hz) for each 3-second EEG sample with 50 % overlay and all electrodes. From the histograms the software derived two FFT single values - The average Total Power (TP) and Frequency at Maximum Power (FMP).RESULTS: It has been shown that during the solution of cognitive tasks the marked changes of ongoing EEG activity appeared. The short lasting and localized amplitude decrease in rhythmic activity (ERD) and the change of EEG frequency were among the most frequent. The ERD extent was determined by an informational content of processed visual stimuli and by the site of scalp-recording electrode. A higher mental load related to the solution of cognitive tasks shifted the average FM to lower frequencies.CONCLUSION: The suitability of an analysis of ongoing EEG activity to uncover differences in people's brain activation patterns when engaged in performing cognitively demanding tasks was proved.
Keywords: Cognitive task/Total Power/Frequency at Maximum Power/ERD